Nanomechanics of a magnetic shuttle device: III Международный семинар по микроконтактной спектроскопииХарьков, Украина, 8–11 сентября 2014 г. - Kulinich, S.I.; Gorelik, L.Y.; Parafilo, A.V.; Shekhter, R.I.; Park, Y.W.; Jonson, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
We show that self sustained mechanical vibrations in a model magnetic shuttle device can be driven by both the charge and the spin accumulated on the movable central island of the device. Different scenarios for how spin- and charge-induced shuttle instabilities may develop are discussed and shown to depend on whether there is a Coulomb blockade of tunneling or not. The crucial role of electronic spin flips in a magnetically driven shuttle is established and shown to cause giant magnetoresistance and dynamic magnetostriction effects.